PENGGUNAAN BAHAN ALAMI UNTUK PENGURANGAN PESTISIDA SEBAGAI UPAYA MENDUKUNG PENCEGAHAN STUNTING - Giovani, Iqbal; Primasari, Winda; Faiz Ridio, Azi (Universitas Islam 45 Bekasi, 2023)
Community service in cabangbungin district, the village of jayabakti, the village of two village asem to reduce the use of pesticides that will cause stunting by the use of a natural biopesticide. It concerns the people of jayabakti whose main job is farmer with an 87% percentage. Farmersotend to continue to use dangerous chemicalopesticides to eradicatopests, so the production of a biopestier is an answer to reducing the use of dangerous chemical pesticides in view of the effects of the useoof chemicalopesticides that are harmful to both human and environmental health. Based on these issues, we had an idea to provide solutions through socialization and practice. Based on the activity of